The cultural heritage spatial data set of Klaipėda old town - Kuklienė, Lina; Jankauskienė, Dainora; Kuklys, Indrius (Geodesy and Cartography, 2012)
The purpose of the thesis is to analyze the main geodetic databases of Lithuania and to create a geodetic database of cultural heritage objects in Klaipėda using program ArcGIS 9.3. The problem is that the geodetic database storing graphical and attributive information about cultural heritage in Klaipeda city has not been created yet. Thus, in order to incorporate GIS technologies into the management of cultural heritage, starting the creation of such a database seems to be a relevant point. The fully completed and regularly updated geodetic database can be used for cultural heritage management, planning, design, road construction, etc. Therefore, the following objectives have been set: 1) describing geo-data collection and input devices; 2) stimulating the geodetic database that introduces information about buildings, building complexes, cemeteries, locations of archaeological and cultural heritage; 3) giving a detailed description of the database creation process; 4) analyzing the need for establishing a geodetic database of cultural heritage objects in Klaipėda. Article in Lithuanian. Saugomų Klaipėdos senamiesčio objektų erdvinių duomenų rinkinys Santrauka. Lietuvoje GIS pagrindu sukurta daug įvairiems tikslams skirtų georeferencinių bei teminių erdvinių duomenų rinkinių. Viena iš šių rinkinių panaudojimo sričių – valstybės registruose esančių duomenų kaupimas. Tokiu principu yra sukurta Kultūros vertybių registro duomenų bazė, kurios pagrindiniai duomenys buvo panaudoti kuriant Klaipėdos miesto kultūros paveldo objektų erdvinių duomenų rinkinį. Siekiant kuo operatyviau įtraukti GIS technologijas į kultūros paveldo objektų tvarkybą, aktualu Klaipėdoje pradėti kurti kultūros paveldo objektų erdvinių duomenų rinkinį. Nuolat atnaujinamas erdvinių duomenų rinkinys palengvins įvairių sričių specialistų atliekamus kultūros paveldo objektų administravimo, teritorijų planavimo, projektavimo, kelių tiesimo ir kitus darbus. Reikšminiai žodžiai: GIS, erdviniai duomenys, erdvinių duomenų rinkinys, kultūros paveldo objektai, atributai. Набор пространственных данных охраняемых объектов старого города Клайпеды Резюме. В Литве на основе ГИС для различных целей создано множество гео-ссылок, а также тематических наборов пространственных данных. Область использования одного из множеств – сбор данных, имеющихся в государственном учете. По такому принципу создана регистрационная база культурных ценностей, основные данные которой были использованы при создании набора пространственных данных объектов культурного наследия города Клайпеды. С целью оперативно обеспечить управление объектами культурного наследия технологиями ГИС следует начать создание набора пространственных данных объектов культурного наследия в Клайпеде. Полностью заполненный и постоянно обновляемый набор пространственных данных облегчит работу специалистов в различных областях: администрировании объектов культурного наследия, планировании территорий, проектировании, строительстве дорог и других. Ключевые слова: ГИС, пространственные данные, набор пространственных данных, объекты культурного наследия, атрибуты.